Perancangan Sistem Informasi Pendaftaran dan Pembayaran Kursus Viacom dengan Metode Prototype - Robby Mukhtar; Fitra Kebesa Miten (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
VIACOM is a well-accredited computer training institution in Jambi City, but its registration and payment system is still inefficient and not responsive to the needs of course participants. The current system is not well integrated, leading to various issues such as data input errors, schedule mismatches, and delays in data updates, which result in operational disruptions and potential revenue loss. Therefore, it is necessary to design a system that can improve staff performance in handling registration and payments, as well as reduce potential disruptions and delays. In this system design, the prototype method is used to allow iterative development, involving users at each stage so the system can be adjusted to meet existing needs and feedback. This approach provides flexibility to improve and optimize the system based on the feedback obtained, with the expectation of producing a system that is more effective, efficient, and in line with user expectations.